Pictionary Game in Promoting Students' Speaking Proficiency - Berlianwirawati, Berlian Wirawati (English Education Department, 2024)
It is undebatable that people learn English in order to be able to use this language in communication, hence, speaking is considered as the most significant indicator of language learning successfulness. Issues in the process of acquiring this skill were solved by big number of previous studies through the employment of game. This research was aimed to investigate the effectiveness of Pictionary game in promoting students’ speaking proficiency. A quantitative of pre-experimental research was applied with one group pre-test and post-test research design. One class of grade 8 students of SMPT Darussalam Reni Jaya Depok participated in this study as the sample. Data were collected through speaking pre-test and post-test. These data were analyzed statistically by using paired-sample t-test. The findings revealed that students achieved better speaking performance in the post-test or after learning by using Pictionary game. Besides, in the significance level of 5% (α = 0.05), t-count of 3.816 was higher than t-table of 1.684. Thus, this research concluded that Pictionary game contributed to the improvement of students’ speaking outcome. In other words, Pictionary game was proven to be effective, used in promoting students’ speaking proficiency.